What's so important about music education? - Goble, J. Scott (New York : Routledge, 2010)
"What's So Important About Music Education? addresses the history of rationales provided for music education in the United States. J. Scott Goble explains how certain factors stemming from the nation's constitutional separation of church and state, its embrace of democracy and capitalism, and the rise of recording, broadcast, and computer technologies have brought about changes in the ways music teachers and concerned others have conceptualized music and its importance in education." "In demonstrating how many of the personal and societal benefits of musical engagement have come to be obscured in the nation's increasingly diverse public forum, Goble also argues for the importance of musical engagement in human life and for the importance of music in education. The book concludes with recommendations for teaching the musical practices of the nation's constituent cultural communities in schools in terms of their respective cultural meanings."--BOOK JACKET
-- "Music" as an academic subject in the public schools of the United States : an inherent cultural tension -- "Culture," "worldview," and pragmatism : the philosophy and semiotic of Charles Sanders Peirce -- A pragmatic conception of musical practices : "music" as a sign of worldview -- Conceptions of music in the United States -- A brief historical survey of concepts of music in music education in the United States -- Community, autonomy, and music education in the postmodern United States : summary and recommendations
Includes bibliographical references and index
Keywords: Music -- Instruction and study -- United States -- Philosophy; Music -- Instruction and study -- United States -- History